Taxonomy-Oriented Domain Analysis of GIS: A Case Study for Paleontological Software Systems - Buccella, Agustina (2019)
Documenting the paleontological process includes data produced by different techniques and protocols, which are used by paleontologists to prospect and eventually find a new fossil. Nowadays, together with the aforementioned data, a great amount of information is also available in terms of georeferenced systems, including contextual as well as descriptive information. However, the use of this information into a model capable of recognizing similarities and differences is still an open issue within the Natural Heritage community. From the software engineering field, software product lines are models that focus on reusing common assets, in such a way that new software developments are only concern on differentiation relying on already modeled (and implemented) systems. This synergy leads us to apply our taxonomy-oriented domain analysis for Software Product Line (SPL) development, when building systems for documenting the paleontological process. In this paper, we introduce the approach for building such software systems, and illustrate its use through a case study in North Patagonia. Findings show promissory results in terms of reuse.